Cost considerations in automating the library. - Bolef, D (1987)
The purchase price of a computer and its software is but a part of the cost of any automated system. There are many additional costs, including one-time costs of terminals, printers, multiplexors, microcomputers, consultants, workstations and retrospective conversion, and ongoing costs of maintenance and maintenance contracts for the equipment and software, telecommunications, and supplies. This paper examines those costs in an effort to produce a more realistic picture of an automated system.